Means of liberalization and beyond: Understanding scheduling approaches in services trade agreements - Ruosi Zhang; Chuwankorn Sasanabanchakul (World Trade Organization (WTO), 2022)
The scheduling approach constitutes a key element of services trade agreements as it is the means to pursue liberalization. This paper provides an overview of the scheduling approaches adopted in 187 trade agreements notified under GATS Article V as of 30 April 2022, analyses the differences between the positive and negative list approaches, and discusses their implications for negotiation strategies and trade policies. Theoretically, both positive and negative list approaches can achieve high level of liberalization as long as governments are willing to open market. We however note in this paper that the scheduling approach is not a stand-alone technique. Rather, it is associated with the design and legal structure of a services trade agreement as well as different core obligations. In addition, establishing a positive or a negative list usually entails different negotiation dynamics and internal consultation processes. With FTAs as important trade policy instruments fast evolving and deepening, governments are becoming more flexible and more "innovative" in their use of scheduling approaches, including creating different hybrid patterns to accommodate their sensitivities in certain sectors, supplementing the positive list with a standstill requirement, or allowing transition from the positive list to the negative list. Governments' practices in FTAs would be inspiring for future services trade negotiations, be it bilateral, plurilateral, or multilateral.
Keywords: F15; 330; Trade in services; scheduling approaches